Realist evaluation of the AKU-SONAM mentorship program - Rehana Rehman; Quratulain Javaid; Saira Khalid; Tazeen Saeed Ali; Rahila Ali (PLoS ONE, 2025)
Background & objectives The context, mechanism, and outcome (CMO) framework is meant to identify specific contextual factors (C) related to organizational and program structure that trigger certain mechanisms (M) involving the unique characteristics of a program, leading to specific outcomes (O). The purpose of this study was to explore the contextual underpinnings, operational processes, and resultant effects of the faculty mentorship program at AKU-SONAM. This exploration involved the context in terms of organizational culture, mechanisms examining processes such as communication between mentors and mentees, quality of relationships, the challenges encountered, and the program’s adaptability to cope up while, outcomes encompassed improvements in interpersonal relationships, career advancement, and skill development. Methods A qualitative exploratory study was conducted at AKU-SONAM, involving in-depth interviews (IDIs) with program leadership and administrators, as well as focus group discussions (FGDs) with mentors and mentees. A semi-structured interview guide, comprising open-ended, introductory, probing, and concluding questions, was developed, validated, and reviewed by experts to ensure its effectiveness and relevance. The process included transcription of interviews, verification through member checks, and thematic analysis where codes and categories were identified and themes, were developed guided by the CMO (Context-Mechanism-Outcome) configuration framework. Results Three IDIs were conducted with administrators and leadership while two FGD were conducted independently with mentors and mentees. Themes for context, mechanism, and outcome were identified. The theme “Navigating Mentorship Challenges in the Professional Landscape” described the Context with subthemes: “Existence of mentorship culture”, Origins and Evolution of Mentoring” “Mentor’s pool, Availability of resources and Mentorship to Seniors. ‘Synergies in Professional Development: From Interdepartmental Collaboration to Mentor-Mentee Connections’ was the theme for mechanisms with subthemes; ‘Fostering Interdepartmental Collaboration’ ‘Building Connections’, ‘sharing of thoughts’, Work Driven Model, Mentor mentee pairing and Selection of mentor. Theme: ‘Cultivating Excellence in the Orchard for Outcome’ emerged from ‘Exchange of Insights in the Orchard of Mentorship’ and ‘Skills Development” constituted the Outcome theme. Conclusions The mentorship program at AKU-SONAM facilitated mentors and mentees to establish connections and exchange ideas. While the mentor-mentee pairing process was clearly outlined, participants emphasized the need to address the challenges encountered by mentees. Although the outcomes were not explicitly clarified, the program contributed to the advancement of the professional development of mentees at AKU-SONAM.